Laboratory Diagnostic Tools for Syphilis: Current Status and Future Prospects - Luo, Yuting; Xie, Yafeng; Xiao, Yongjian (Frontiers in Cellular and Infection Microbiology, 2021)
With the increasing number of patients infected with syphilis in the past 20 years, early diagnosis and early treatment are essential to decline syphilis prevalence. Owing to its diverse manifestations, which may occur in other infections, the disease often makes clinicians confused. Therefore, a sensitive method for detecting T. pallidum is fundamental for the prompt diagnosis of syphilis. Morphological observation, immunohistochemical assay, rabbit infectivity test, serologic tests, and nucleic acid amplification assays have been applied to the diagnosis of syphilis. Morphological observation, including dark-field microscopy, silver-staining, and direct fluorescent antibody staining for T. pallidum, can be used as a direct detection method for chancre specimens in primary syphilis. Immunohistochemistry is a highly sensitive and specific assay, especially in the lesion biopsies from secondary syphilis. Rabbit infectivity test is considered as a sensitive and reliable method for detecting T. pallidum in clinical samples and used as a historical standard for the diagnosis of syphilis. Serologic tests for syphilis are widely adopted using non-treponemal or treponemal tests by either the traditional or reverse algorithm and remain the gold standard in the diagnosis of syphilis patients. In addition, nucleic acid amplification assay is capable of detecting T. pallidum DNA in the samples from patients with syphilis. Notably, PCR is probably a promising method but remains to be further improved. All of the methods mentioned above play important roles in various stages of syphilis. This review aims to provide a summary of the performance characteristics of detection methods for syphilis.